2015
DOI: 10.1177/1096348015584441
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Engagement in Online Social Network on Susceptibility to Influence

Abstract: The effect of consumer participation in online social networking activities on their susceptibility to influence is investigated in a context of restaurant consumption. This research identified a positive relationship between consumers engagement in social networking sites (SNS) on their susceptibility to global consumption influence, which is a multidimensional factor consisting of conformity to trend, social prestige, and quality perception. Furthermore, consumer engagement in SNS and susceptibility to globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 83 publications
0
44
2
Order By: Relevance
“…The recent research demonstrates the positive influence of customer engagement on businesses, such as enhanced customer relationships and brand attitude and higher future purchasing intentions (e.g., Brodie et al, 2013; Hollebeek et al, 2014; Tussyadiah, Kausar, & Soesilo, 2015). For example, So, King, Sparks, and Wang (2016) conducted two studies on retail brands and concluded that customer engagement has a significant impact on customer–brand relationship quality and customer loyalty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The recent research demonstrates the positive influence of customer engagement on businesses, such as enhanced customer relationships and brand attitude and higher future purchasing intentions (e.g., Brodie et al, 2013; Hollebeek et al, 2014; Tussyadiah, Kausar, & Soesilo, 2015). For example, So, King, Sparks, and Wang (2016) conducted two studies on retail brands and concluded that customer engagement has a significant impact on customer–brand relationship quality and customer loyalty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Remuneration company messages include specific information which is directly or indirectly associated with various benefits for customers including special promotions, trials and other offers (Cvijikj & Michahelles, 2013;Luarn et al, 2015;Kwok & Yu, 2016). These messages can encourage social contagion process and in turn, generate customer sociability behaviour on a company's Facebook page (Tussyadiah, Kausar, & Soesilo, 2015). An example of remuneration messages is as follows: "[...] share this message and wait for the 9th of October, when the winner will be announced!".…”
Section: Content Type Of Company Messagesmentioning
confidence: 99%
“…This study explored the relationships among SNSs’ activities, customers’ psychological needs, perceived well-being, and their brand usage intent. Different from previous SNSs’ studies that investigated the network externalities, marketing effectiveness, or consumer engagement (Kang & Young, 2016; Leung et al, 2015; Tussyadiah et al, 2018), this study examined the relationships between customers’ SNSs’ activities and their psychological needs. Results identified a possible mechanism that explained a positive influence of SNSs’ activities on customers’ well-being and their brand usage intent.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the number of friends on SNSs influenced people’s psychological outcomes, such as life satisfaction (J. H. Kim & Lee, 2011). Previous hospitality and tourism literature has examined the role of SNSs on customers’ behaviors (e.g., Tussyadiah, Kausar, & Soesilo, 2018); however, it was still puzzling what made customers fulfill their psychological needs that fostered their well-being perceptions when customers engaged with SNSs to share their hotel experiences.…”
Section: Introductionmentioning
confidence: 99%